Research on fault monitoring of belt conveyor based on FBG sensor - Xinqiu FANG; Yang WU; Yang SONG; Ningning CHEN; Yulong FENG; Haotian FENG; Dexing HE; Fukang QIAO (Meitan kexue jishu)
The fault monitoring of belt conveyors serves as a pivotal tool in preventing safety incidents, enhancing production efficiency, and facilitating the intelligent operation of equipment. This comprehensive study delves into the multi-sensor fault monitoring of belt conveyors utilizing Fiber Bragg Gratings (FBGs), examining aspects such as common fault analysis, the composition of integrated protection systems, the design and analysis of fiber-optic sensor arrays, and the design and material selection of core sensing elements.Firstly, to address the shortcomings of traditional monitoring methods, including the inability to quantify faults, inadequate real-time performance, and weak data fusion capabilities, an FBG-based integrated protection system for belt conveyors is proposed. This system underscores the cruciality of designing a fiber-optic sensor array as a fundamental prerequisite for system establishment.Secondly, building upon an analysis of the root causes and manifestations of common faults in belt conveyors, a series of fault monitoring sensors are devised, with FBG-based equal-strength cantilever beams serving as the core sensing elements. These sensors constitute the fiber-optic sensor array within the integrated protection system, enabling real-time and quantitative fault monitoring.Thirdly, theoretical analyses and Ansys finite element simulations are conducted to thoroughly investigate the dimensional design and material selection of FBG-based equal-strength cantilever beams. The influencing factors on sensitivity and accuracy are analyzed within the sensing model, guiding the determination of the structural dimensions of the sensing elements. Nylon 6 is selected as the optimal material for fabrication.Finally, experimental validation is performed to assess the structural effectiveness, sensitivity, and stability of the FBG-based equal-strength cantilever beams. In sensitivity tests, the sensing elements exhibit exceptional linear response characteristics, with a theoretical sensitivity of 52.9780 N/nm and an actual sensitivity of 38.1157 N/nm. In repeatability tests, an average repeatability error of merely 1.002% is recorded, demonstrating robust repeatability and stability. Temperature sensitivity and compensation tests verify the linear correlation of FBGs in temperature measurement, emphasizing the necessity of temperature compensation for enhancing sensing sensitivity. Even under minor temperature variations, the compensation mechanism effectively boosts sensitivity by 0.6%.The designed fiber-optic sensor array resolves the challenge of real-time and quantitative fault perception in current belt conveyor operations, providing a solid data foundation for intelligent sensing and control. This research not only contributes to reducing belt conveyor failure rates and enhancing production efficiency but also propels the coal mining industry towards automation and intelligence.